A World Is Ending - Bryant, Levi R. (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Levi R. Bryant Title (English): A World Is Ending Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 50-54 Page Count: 5 Citation (English): Levi R. Bryant, “A World Is Ending,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 50-54.